Renewal of Islamic Education in Traditionalist Works in Minangkabau: Sheikh Khatib Muhammad Ali and the Traditionalist Intellectualism People - Junaidi; Hanani, Silfia; Eefendi, Darno; Yuliana, Diva Dwi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Few studies on the intellectual contribution of old people have been conducted, resulting in a research gap. The majority of studies tended to investigate younger people as the driver of renewal, while educational ideas from the old people are used to be neglected. This study aims to explore the educational thought of Sheikh Khatib Muhammad Ali as one of the old intellectuals, through his traditionalist book entitled “Syair Irsyadiyah”. This study employs a hermeneutic approach to literature analysis to get more insights into the meaning of written texts precisely, so that there is no gap in the reader's understanding of the author of the original text. Primarily, data were collected from the book “Syair Irsyadiyah”, supported with other related literature, such as books, articles, and previous research findings. The findings demonstrated that Sheikh Khatib Muhammad Ali is a traditionalist and a pioneer who balances the views of modernists and traditionalists in Minangkabau Islamic education This is demonstrated by his ideas about education, as follows: 1) Sheikh Khatib Muhammad Ali created and implemented a new curriculum that includes structured subjects, standardized science, systematic teaching methods, and learning evaluation. 2) Sheikh Khatib Muhammad Ali also made up his own books to be taught in his school while the religious schools preferred to maintain teaching classical books originating from Middle Eastern scholars from the middle ages. 3) Santri needs to be of high moral character since learning is a necessity. His concepts indicate the effort to renew Islamic studies by making religious knowledge and general knowledge balanced, using systematic and measurable teaching materials, and developing students’ good character.